2016
DOI: 10.1089/aid.2015.0318
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Group O Genotypes and Phenotypes: Relationship to Fitness and Susceptibility to Antiretroviral Drugs

Abstract: Despite only 30,000 group O HIV-1 infections, a similar genetic diversity is observed among the O subgroups H (head) and T (tail) (previously described as subtypes A, B) as in the 9 group M subtypes (A-K). Group O isolates bearing a cysteine at reverse transcriptase (RT) position 181, predominantly the H strains are intrinsically resistant to non-nucleoside reverse transcriptase inhibitors (NNRTIs). However, their susceptibility to newer antiretroviral drugs such as etravirine, maraviroc, raltegravir (RAL), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…10 Similarly, HIV-1 group O isolates are naturally resistant to NNRTIs and show decreased sensitivity to some protease and integrase inhibitors. 11 Hence, options available to treat patients infected with these viruses are currently very limited. Thus, a continuing need exists for development of novel drugs and regimens in order to address the tolerability and long-term safety concerns associated with current treatment options, and the emergence of drug resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Similarly, HIV-1 group O isolates are naturally resistant to NNRTIs and show decreased sensitivity to some protease and integrase inhibitors. 11 Hence, options available to treat patients infected with these viruses are currently very limited. Thus, a continuing need exists for development of novel drugs and regimens in order to address the tolerability and long-term safety concerns associated with current treatment options, and the emergence of drug resistance.…”
mentioning
confidence: 99%
“…An additional challenge is that HIV-2 isolates are naturally resistant to NNRTIs and fusion inhibitors (FIs) and present a decreased sensitivity to most protease inhibitors (PIs) . Similarly, HIV-1 group O isolates are naturally resistant to NNRTIs and show decreased sensitivity to some protease and integrase inhibitors . Hence, options available to treat patients infected with these viruses are currently very limited.…”
mentioning
confidence: 99%
“…Concerning HIV-1 group O, the natural genetic polymorphism is now well determined by comparison with HIV-1 group M [ 76 ]. The main issue since 1997 was the natural resistance associated with non-nucleoside RT inhibitors (NNRTIs) [ 78 , 79 , 80 , 81 ] through the well-known Y181C. This mutation was present in 54 to 79% of the strains, depending on the studies [ 76 , 82 ], and is likely to be subgroup-dependent (H or T) [ 83 , 84 ].…”
Section: Antiretroviral Agentsmentioning
confidence: 99%
“…This hypothesis has already been demonstrated for etravirine. Indeed, its phenotypic activity on group O strains was less affected (fold change (FC) of 10) than that of nevirapine (FC of 89) or efavirenz (FC of 42) [ 79 ]. It has also been demonstrated that additional mutations on the RT region could decrease drug susceptibility.…”
Section: Antiretroviral Agentsmentioning
confidence: 99%
“…Chimeric contigs can closely resemble expressed transcripts, but patterns such as those between co-evolving sites [ 42 ], remapped read counts [ 43 , 44 ] and polymorphisms [ 45 , 46 ] become obscured, and chimera presence has a poorly quantified impact on data analysis [ 41 , 47 , 48 ]. In relation to transcriptomics, included within data analysis is at times the characterization of gene differential expression patterns, where the primary signal utilized are the differences in mapped read counts, across datasets allocated to differing conditions, relative to sequences within a reference [ 49 ].…”
Section: Introductionmentioning
confidence: 99%